An Analysis of Factors of Culture Shock and Culture Shock Stages Occurred in the Main Character of She Smells of Turmeric Novel - Syifa Aisyah Likandi; Arie Sugiyartati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
Culture shock occurs because of the culture gap and differences, such as habit, behaviour, values, religion, tradition, and other cultural aspects. The symptoms of a sojourner who fights the shock are explained by the factors of culture shock and how they combat the cultural changes that are causing the shock which described in four stages. This study aims to elucidate the existence factor of culture shock and the stage of culture shock that corresponds to the protagonist of the novel